Factors Determining Consumer Purchase Intention on TikTok Shop: A Literature Review - Ridha, Rizkillah; Nadlifatin, Reny (Jurnal Nasional Teknologi dan Sistem Informasi, 2025)
The trend of commerce through mobile apps has encouraged many social commerce companies to capitalize on this lucrative market opportunity. As a social commerce platform, TikTok Shop significantly influences consumer behavior, especially regarding purchase intention. Purchase intention has been a topic of interest in marketing and consumer behavior for many years. However, most of the previous studies used more quantitative approaches. This research aims to fill the gap in the literature by exploring the factors that influence consumer purchase intention in TikTok Shop social commerce. The method used is a literature study, which summarizes findings from 36 relevant articles. The results show that twenty factors influence consumer purchase intention. These factors include various aspects, ranging from trust to technical features of the TikTok Shop platform. As such, this research makes an essential contribution to understanding the dynamics of consumer purchase intentions in the growing era of digital commerce.